2021
DOI: 10.1088/1361-6641/abd489
|View full text |Cite
|
Sign up to set email alerts
|

New barrier layer design for the fabrication of gallium nitride-metal-insulator-semiconductor-high electron mobility transistor normally-off transistor

Abstract: This paper reports on the fabrication of an enhancement-mode AlGaN/GaN metal-insulator-semiconductor-high electron mobility transistor with a new barrier epi-layer design based on double Al0.2Ga0.8N barrier layers separated by a thin GaN layer. Normally-off transistors are achieved with good performances by using digital etching (DE) process for the gate recess. The gate insulator is deposited using two technics: plasma enhance chemical vapour deposition (sample A) and atomic layer deposition (sample B). Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The second step is oxide etching by hydrochloric acid (HCl) solution or dry BCl 3 plasma etching. [22][23][24][25][26][27][28][29] It was reported that the digital etching depth per cycle is self-limiting and depends primarily on the oxidation depth with different plasma power and time settings. 23) Therefore, the gate recess etching depth can be controlled strictly by the etching cycles.…”
mentioning
confidence: 99%
“…The second step is oxide etching by hydrochloric acid (HCl) solution or dry BCl 3 plasma etching. [22][23][24][25][26][27][28][29] It was reported that the digital etching depth per cycle is self-limiting and depends primarily on the oxidation depth with different plasma power and time settings. 23) Therefore, the gate recess etching depth can be controlled strictly by the etching cycles.…”
mentioning
confidence: 99%